Incidental findings in pancreas screening programs for high‐risk individuals: Results from three European expert centers. Issue 5 (1st June 2019) - Ibrahim, Isaura S; Brückner, Catharina; Carrato, Alfredo; Earl, Julie; Inderson, Akin; de Vos tot Nederveen Cappel, Wouter H; Mintziras, Ioannis; Matthäi, Elvira; Figiel, Jens; Wasser, Martin; Moreau, Hans; Bonsing, Bert; et al.
Abstract : Background: Widespread abdominal imaging has led to a substantial increase in the detection of incidentalomas. Currently, an increasing number of centers offer surveillance of the pancreas to individuals at high risk (IARs) of pancreatic ductal adenocarcinoma (PDAC). Objective: The aims of this study were to evaluate the frequency and type of incidental findings in a magnetic resonance imaging (MRI)‐based surveillance program for IARs for PDAC, and to discuss the benefit of detecting these lesions. Methods: The outcome of MRI screening was reviewed in 568 individuals from three long‐term pancreas surveillance programs conducted at three large European expert centers. All MRIs were studied in detail for the presence of incidental lesions. Results: The most common lesions were liver cysts, renal cysts and liver hemangioma, which together comprised 75% of all lesions. Only five (0.9%) patients underwent surgery for a benign lesion. Cancer was detected in 11 patients (1.9%); early detection of tumors was beneficial in at least five cases. Conclusion: The present study demonstrates that extrapancreatic incidentaloma is a common finding in IARs for PDAC, but rarely requires additional treatment. CDKN2A‐p16‐Leiden mutation carriers were the only patient group found to harbor a substantial number of cancers, and detection resulted in benefit in several cases.